2011
DOI: 10.1099/ijs.0.023267-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Bacillus amyloliquefaciens clades associated with strains DSM 7T and FZB42T: a proposal for Bacillus amyloliquefaciens subsp. amyloliquefaciens subsp. nov. and Bacillus amyloliquefaciens subsp. plantarum subsp. nov. based on complete genome sequence comparisons

Abstract: The whole-genome-sequenced rhizobacterium Bacillus amyloliquefaciens FZB42T (Chen et al., 2007) and other plant-associated strains of the genus Bacillus described as belonging to the species Bacillus amyloliquefaciens or Bacillus subtilis are used commercially to promote the growth and improve the health of crop plants. Previous investigations revealed that a group of strains represented a distinct ecotype related to B. amyloliquefaciens; however, the exact taxonomic position of this group remains elusive (Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
186
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(200 citation statements)
references
References 53 publications
9
186
0
5
Order By: Relevance
“…plantarum FZB42 T and 'B oryzicola' KACC 18228 are consistent with the strains belonging to the same species (Borriss et al, 2011;Chung et al, 2015;Madhaiyan et al, 2010;Ruiz-García et al, 2005). The previously published fatty acid methyl ester data are slightly variable, but the primary fatty acid components are the same.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…plantarum FZB42 T and 'B oryzicola' KACC 18228 are consistent with the strains belonging to the same species (Borriss et al, 2011;Chung et al, 2015;Madhaiyan et al, 2010;Ruiz-García et al, 2005). The previously published fatty acid methyl ester data are slightly variable, but the primary fatty acid components are the same.…”
supporting
confidence: 74%
“…Because the valid publication of B. velezensis (Ruiz-García et al, 2005) predates the publication of B. methylotrophicus (Madhaiyan et al, 2010), B. amyloliquefaciens subsp. plantarum (Borriss et al, 2011) and 'B. oryzicola' (Chung et al, 2015), we propose that B. methylotrophicus, B. amyloliquefaciens subsp.…”
Section: Phylogenomic Analysis Of Bacillus Velezensismentioning
confidence: 95%
“…The cell-wall peptidoglycan contained meso-diaminopimelic acid. The total cellular fatty acid profiles showed a large amount of branched fatty acids; the major components (>5.0 %) were anteiso-C 15 : 0 (34.8 %), iso-C 15 : 0 (21.9 %), iso-C 17 : 0 (15.7 %), anteiso-C 17 : 0 (11.4 %) and C 16 : 0 (9.7 %) ( the close relatives B. amyloliquefaciens, B. atrophaeus and B. velezensis determined in this study were consistent with previously reported profiles (Borriss et al, 2011;Nakamura, 1989;Ruiz-García et al, 2005). B. nakamurai could not be distinguished from its closest related species on the basis of fatty acid profiles.…”
supporting
confidence: 92%
“…In this way W23 more closely resembles the Gram-positive pathogen Staphylococcus aureus (Qian et al, 2006). Understanding the enzymology (Brown et al, 2010) and regulation (Minnig et al, 2005) of W23 wall synthesis remains an ongoing concern. W23 also remains a useful comparison to 168 for the study of B. subtilis taxonomy, ecology and evolution, since W23 is the best-characterized member of the subspecies spizizenii and 168 of subspecies subtilis (Nakamura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%